Rzeczpospolita – pojęcie i idea w dyskursie politycznym Rzeczypospolitej Obojga Narodów. Rekonesans - Grześkowiak-Krwawicz, Anna (Odrodzenie i Reformacja w Polsce, 2012)
Rzeczpospolita – The Terms and the Concept in the Political Discourse of the Polish–Lithuanian Commonwealth. Reconnaissance This article is an attempt to analyze the significance and function of the concept Rzeczpospolita (“Republic” or “Commonwealth”), the most popular word in Old–Polish political discourse from the end of the 16th century to the 18th century. It illustrates the wealth of meanings of the term, which was used to describe the state, the society, and the political system. The author tries to present the distinctive Polish phenomenon that involved transferring the classical idea of a res–publica, as a civil community, to the realities of the Polish–Lithuanian Commonwealth – a transfer so faithful that one may even call it a kind of usurpation. This had an impact on the understanding of the concept, which at a certain point (the 17th century) became narrowed down to just the community of the nobility. It was also crucial for the concept’s persistence – despite the changes that occurred over two centuries, despite the modernization of political discourse in the 18th century, the state understood qua Rzeczpospolita never became something external to the citizen, it was always perceived as a civil community, more the Roman cititas than the French l’etat.